Students Readiness in Online Lectures During the Pandemic: What is the Ideal Lecture Model? - Dwiharyadi, Anda; Afni, Zalida; Aulia, Rentih (The International Journal of Business Review (The Jobs Review), 2020)
Abstract. This study identifies the readiness, perceptions and preferences of students in facing online learning. This study will also propose an effective online learning model design. Data obtained from 362 students through a questionnaire using a likert scale. The results shows that in general the students are ready to carry out the process of online learning. Besides using a live conference media, students prefer the use of teaching videos made by lecturers himself as an alternative method when quota and internet signals are the main problems. The distribution of learning materials should be carried out at least one day before the learning schedule. Meanwhile, the allocation of lecture time is not too much in the attendance process. Furthermore, the evaluation process is also carried out for each material topic. Thus, the focus of the on learning model should consider teaching media, material distribution, time allocation and learning evaluation process.Â Keywords: readiness, preferences, on line learning; effective